Divine Life : Sri Aurobindo's Experience - Basu, Arabinda (Journal of Dharma, 1987)
Divine Life means different things to different people. A highly moral or ideal istic life is divine life according to some; for others it is the religious life in which man's consciousness is turned towards God, as a consequence of which one has a certain calm and quietude of mind and life, an inwardness centred in the Deity. It is true the divine life is primarily the inner life, the life of the spirit in which man's spiritual soul and the supreme Spirit are united in some way. This union must have some influence and impact on the outer nature of man though it does not spiritualise it. Nevertheless one who has realized God lives in God in whatever way he may exist in other people's estimation. The divine life may also be understood as existence in some other world where the limitations and imperfections of this earthly life do not oppress the soul of man, where ignorance and error, evil and suffering have no place. 10 Indian terms, this may be life in Goloka Vrindacana, Shiva-or Vishnu-or Brahmaloka,